2007
DOI: 10.1897/07-168
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of leaf decomposition in copper contaminated freshwater mesocosms

Abstract: The influence of copper on leaf litter decomposition was examined in experimental streams. Controls and three levels of contamination (5, 25, and 75 microg/L) were tested in triplicate in 20-m-long mesocosms. Equal quantities of alder, maple, and oak leaves were enclosed in mesh bags and placed in the upper and lower mesocosm sections that exhibited different habitat characteristics (shallow with pebble substrate or deep with fine substrate and macrophytes, respectively). Decomposition rate in the upper sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…; Duarte, Pascoal & Cássio ) may have reduced the competitive pressure for fungi resulting in the higher fungal biomasses. This may also explain the observed trends to an increased fungal spore production (Roussel, Chauvet & Bonzom ; Sridhar & Bärlocher ) and a higher number of fungal species on Cu‐exposed leaf discs (Table ). Likewise, Bundschuh et al .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…; Duarte, Pascoal & Cássio ) may have reduced the competitive pressure for fungi resulting in the higher fungal biomasses. This may also explain the observed trends to an increased fungal spore production (Roussel, Chauvet & Bonzom ; Sridhar & Bärlocher ) and a higher number of fungal species on Cu‐exposed leaf discs (Table ). Likewise, Bundschuh et al .…”
Section: Discussionmentioning
confidence: 86%
“…), some studies assessed leaf‐associated microbial community composition and functioning in response to Cu exposure (Tattersfield ; Duarte et al . ; Roussel, Chauvet & Bonzom ; Duarte et al . ; Pradhan et al .…”
Section: Introductionmentioning
confidence: 99%
“…That the fungi in our experiment were negatively affected by the addition of Al flakes to microcosms accords with previous studies, where Al was found to affect fungal development and sporulation (Chamier et al ., ; Roussel et al ., ; Cornut et al ., ). The decline in fungal biomass contrasts, however, with the resistance of G. pulex to Al flakes.…”
Section: Discussionmentioning
confidence: 97%
“…This outcome accords with previous studies that found FR to be a robust and sensitive indicator of stressful conditions experienced by G. pulex (e.g. Forrow & Maltby, ; Maltby et al ., ; Zubrod et al ., ), including stress imposed by metal exposure (Maltby & Crane, ; Roussel et al ., ; Alonso et al ., ). Consequences at the ecosystem level, that is beyond altered FRs and other ramifications for gammarids not captured by our survival and body mass assessments, are potentially far‐reaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation